Amamiku, a new genus for the true freshwater crab, Candidiopotamon amamense Minei, 1973 (Decapoda: Brachyura: Potamidae), from the Central Ryukyu Islands, Japan - Naruse, Tohru; Segawa, Ryoko; Shokita, Shigemitsu (Zootaxa, 2004)
Amamiku, a new genus, is established for Candidiopotamon amamense Minei, 1973. Amamiku is morphologically most closely related to Candidiopotamon Bott, 1967, but they can be differentiated by their male first pleopods. A key to the genera of the Japanese true freshwater crabs is also provided.